ANALISIS KEMAMPUAN METAKOGNISI SISWA TERHADAP MATERI BANGUN RUANG DI SD - Lenny Gusti Anggraini; Nirwana Anas (FIP Unimed, 2019)
ABSTRACTThis study aims to analyze the extent to which the metacognition abilities of fifth grade elementary school students in mathematics subject to material in space. This type of research is descriptive qualitative, the subjects in the study were elementary school students class V-b, amounting to 31 people. Data was collected using a questionnaire that refers to the rubric Metacognitive Awareness Inventory (MAI). The results showed that the ability of metacognition in fifth grade elementary school students showed that the ability of 80% cognitive knowledge and 81% cognitive regulation with this can be said to be very related.Keywords: Build Space, Metacognition and Regulation ABSTRAKPenelitian ini bertujuan untuk menganalisis sejauh mana kemampuan metakognisi siswa SD kelas V dalam pelajaran matematika materi bangun ruang. Jenis penelitian ini ialah deskriptif kualitatif, subjek dalam penelitian adalah siswa SD kelas V-b yang berjumlah 31 orang. Pengumpulan data dilakukan menggunakan angket yang mengacu pada rubrik Metacognitive Awareness Inventory (MAI). Hasil penelitian menunjukkan bahwa kemampuan metakognisi pada siswa SD kelas V menunjukkan bahwa kemampuan pengetahuan kognisi 80% dan regulasi kognisi 81% dengan ini dapat dikatakan sangatlah berhubungan. Kata Kunci: Bangun Ruang, Metakognisi dan Regulasi